UJI PUPUK ORGANIK DAN ANORGANIK PADA LAHAN SUB-OPTIMAL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum sp) (Test of Organic and Inorganic Fertilizers on Sub-Optimal Land Against Growth and Production of Chili (Capsicum sp) Plants - Akhmad Sopian; Abdul Rofik (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
The aim is to know the potential of chilli production in sub obtimal soil and to know the effect of organic and inorganic fertilizers on the growth and production of chilli plants. The method used in this study was in the form of a field experiment arranged in a Randomized Block Design (RCBD) with a 2 x 4 Factorial experiment with 4 replications. The first factor is organic fertilizer consisting of: B0: without manure Bk: 500 grams / staple. The second factor is inorganic fertilizer consisting of: P0: 10 g urea (Control), P1: 10 g urea + 10 g SP-36 + 10 g Kcl, P2: 10 g urea + 15 g SP-36 + 15 g Kcl, P3: 10 g urea + 20 g SP-36 + 20 g Kcl. The results showed that organic fertilizer treatment significantly affected the growth of height, diameter, number of branches, age of flowering, and the number of fruit of cayenne pepper. Inorganic fertilizer treatment (SP-36 and KCL) had no significant effect on the growth and production of cayenne plants. The best interaction is the combination of B0P1 fertilizer (urea + SP-36 + KCL) and BKP0 (urea + manure) treatment. The application of organic and inorganic fertilizers separately is stronger than when applied together. Damage to plants caused by curly diseases in the rainy season due to poor drainage (sub-optimal) land conditions. Application of organic and inorganic fertilizers to be applied separately. Optimal land management is needed by making good drainage to reduce the level of attack of critical diseases, especially in the rainy season.